Crystal structure of poly[(μ2-1,3-bis(imidazol-1-ylmethyl)benzene-κ2N:N′)(nitrato-κ1O)cadmium(II)] — water (2/1), C28H32CdN10O7 - Wang Bo (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C28H32CdN10O7, triclinic, P1̄ (no. 2), a = 8.2649(5) Å, b = 9.7841(6) Å, c = 10.0808(6) Å, α = 94.069(7)°, β = 104.912(7)°, γ = 97.695(7)°, V = 775.89(9) Å3, Z = 1, Rgt(F) = 0.0432, wRref(F2) = 0.1140, T = 293(2) K.